The effect of linear and daily undulating periodized resistance training on the neuromuscular function and the maximal quadriceps strength - NASRIN ABDI; MOHAMMAD REZA HAMEDINIA; ZAHRA IZANLOO; NOSRATOLLAH HEDAYATPOUR (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: ‪The purpose of this study was to investigate the effects of 9 weeks' resistance training utilizing a daily undulating periodization (DUP) program versus a linear periodization (LP) program on concentric and isometric muscle strength and neuromuscular function of the quadriceps muscle. Material and methods: ‪30 male subjects (age = 21.7 ±2.5 yr, body mass = 71.4 ±11.9 kg, height =1.77 ±0.09 m) participated in the study. Subjects were randomly divided into DUP and LP training groups. Both the DUP and LP training group performed leg press exercise 3 times per week. Volume and intensity were equated for each training program. However, the periodization type was different between the two groups. Additionally, the maximal isometric voluntary contraction (MIVC) of the quadriceps muscle and the associated electromyography (EMG) activity were recorded before and after 9 weeks of the DUP and LP training programs. Results: ‪The DUP training program resulted in a greater increase (50.1% ±10.1) in quadriceps isometric strength compared with the LP training program (35.5% ±7.3; F = 7.6, p < 0.025). Accordingly, EMG activity of the quadriceps muscle after 9 weeks of the DUP training program was significantly larger than that observed after the LP training model (F = 7.5, p < 0.05). Conclusions: ‪Resistance training using a DUP program is more effective than a LP program to elicit neuromuscular activity and muscle strength.